Neoliberalism, imperialism and conservatism: tangled logics of educational inequality in the global South. Issue 2 (4th March 2019) - Windle, Joel
ABSTRACT: Accounts of neoliberalism in education frequently evoke a universal trend, with insufficient attention to context, as well as routinely presenting the 'pre-neoliberal' as the ideal. This paper argues that studies of neoliberalism, concentrated in the global North, frequently ignore the distinctive forms and histories of neoliberalism in the global South, as well as its connections to other logics of power, which are illustrated using examples of schooling in Brazil. The differing weight of neoliberal politics and policies across geopolitical boundaries suggests caution in casting neoliberalism as a unique institutional setting for contemporary educational inequalities or attributing all educational conservatism to neoliberalism. A conceptual contribution is provided by proposing a multi-scalar approach to educational inequalities, in which educational sites, events and practices are considered in terms of nexus.